Pola dan Intensitas Pigmentasi Serta Fotosintesis pada Tanaman Hias Daun Caladium pada Tingkat Naungan Berbeda: Pigmentation Pattern and Intensity and Photosynthesis of Ornamental Caladium at Different Shading Levels - Yanuar, Ai Ika Ayu; Hamim, Hamim; Laelasari; Ratnadewi, Yuliana Maria Diah (Jurnal Sumberdaya Hayati, 2025)
Caladium, a member of the Araceae family, is known for its diverse leaf colors and patterns, referred to as variegation. This study aimed to examine the relationship between pigmentation patterns, variegated areas, and leaf anatomy, chlorophyll content, and photosynthetic rate under different light conditions. Two light treatments were applied, full sun (0% shade, 37,500 lux) and 70% shade (12,000 lux), using direct morning sunlight. Seven distinct types of Caladium were used in the experiment. Photosynthetic rate was measured using a LI-6400 portable photosynthesis system at Photosynthetic Photon Flux Densities (PPFD) of 100, 400, and 800 µmol m-2 s-1. Pigment analysis included quantification of chlorophyll, carotenoids, and anthocyanins, while morphological assessments focused on leaf size, variegated area, and leaf thickness. Plants exposed to higher light intensity developed smaller, thicker leaves with mostly larger proportion of variegated area. Chlorophyll, carotenoid, and anthocyanin contents varied depending on plant type and light treatment. The net photosynthetic rate (Pn) increased with higher PPFD and was greater in unshaded conditions. Among the plant types, V3 and V4 exhibited characteristics typical of shade-adapted species, while V6 showed traits of sun-loving plants. Overall, the study demonstrated that variegated Caladium plants maintain comparable net photosynthetic rates despite differences in pigmentation patterns and variegation intensity.